META-ANALYSIS OF THE EFFECT OF SCRAMBLE TYPE COOPERATIVE LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES AT ELEMENTARY SCHOOLS - Afifah Endah Nurhasanah; Nafiah; Akhwani; Syamsul Ghufron (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to re-analyze the effect of scramble learning model to improve students’ learning outcomes at elementary schools. Scramble learning model refers to a game of arranging the scrambled words and letters in order to form a certain meaningful word. The scramble learning can train students to be creative to arrange random words and sentences in order. This study utilized a meta-analysis method. At the first stage, the researcher formulated the problem, then, sought the existing and relevant research to be analyzed. The technique of data collection in this study was a non-test, namely the documentary analysis method, by searching for electronic journals on Google Scholar with the criteria of comparative journals or articles. There were 11 articles that fulfilled the criteria for this research. The results of the journal analysis indicated that scramble learning model could improve the students' cognitive learning outcomes. This was proved by the average difference of the results of the pre-test and post-test which was 24.9. To strengthen the results, these data were tested by IBM SPSS statistical program 16 for windows with paired sample T test. Based on the result of this test, it was revealed that H1 was accepted which implied that the scramble learning model had an effect on students’ learning outcomes with the value of sig 0.00 <0.05.